2021
DOI: 10.3390/nano11010205
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Green-Synthesized Silver Nanoparticles Using Areca catechu Extract against Antibiotic-Resistant Bacteria

Abstract: In this work, the antibacterial activity of silver nanoparticles (AgNPs) synthesized using Areca catechu extracts against three species of antibiotic-susceptible and three species of resistant bacteria was investigated. The effects of this plant were more promising when compared with other medicinal plants tested. The hydrothermal extract of Areca catechu was mixed with silver nitrate to synthesize AgNPs. The synthesized particle characteristics were analyzed by UV–Vis spectrophotometry, scanning electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 26 publications
(27 reference statements)
1
21
0
Order By: Relevance
“…Moreover, hemolytic evaluations of BG-AgNPs against human RBCs demonstrated that the BG-mediated AgNPs were highly biocompatible to mammalian cells. To our best knowledge, the inhibition efficiency of A-BG-AgNPs against drug-resistant Gram-negative bacterial strains is superior to the other plant extract-mediated AgNPs from previous studies [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, hemolytic evaluations of BG-AgNPs against human RBCs demonstrated that the BG-mediated AgNPs were highly biocompatible to mammalian cells. To our best knowledge, the inhibition efficiency of A-BG-AgNPs against drug-resistant Gram-negative bacterial strains is superior to the other plant extract-mediated AgNPs from previous studies [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 86%
“…This implies that green‐synthesised nanoparticles are more active against microbial strains than are crude extracts. It is evident from earlier research that AgNPs‐synthesised nanoparticles from Areca catechu exhibited potential activity against antibiotic‐resistant bacteria [35]. The compound phlorotannin from brown seaweeds also exhibits good antiviral, antibacterial, antifungal, and larvicidal activities [36].…”
Section: Discussionmentioning
confidence: 99%
“…To obtain silver nanoparticles, several analytical techniques were utilized, including UV-vis, TEM, XRD, zeta potential, and FTIR. In general, the sizes of AgNPs in green-route were larger compared with the particles synthesized by chemical methods ( Choi et al, 2021 ). Priyanka Basera reported that AgNPs prepared by Cymbopogon citratus were about 35 nm ( Khan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%